Artemis Fowl : The Last Guardian - Book 8 - Colfer, Eoin (New York : Disney*Hyperion, 2012)
Teenage genius Artemis Fowl and his arch rival Opal battle to the last in this eighth and final book in series.
Keywords: Adventure and adventurers -- Fiction; Fairies -- Fiction; Genius -- Fiction; Magic -- Fiction; Space and time -- Fiction; Fantasy fiction